Optimize shift scheduling using pinch analysis - Foo, Dominic C. Y. (Animo Repository, 2010)
The newly developed pinch analysis technique for short-term, batch-process scheduling can be applied to the short-term scheduling of workers, in order to address a common challenge that impacts optimum human-resources management. The common graphical composite curves used in pinch analysis are particularly helpful to identify allocation issues and provide insights on possible scheduling adjustments or task reassignments efficiently. The pinch diagram plots the resources and activities separately, so that they can be manipulated independently. The graphical technique provides the same insights common to pinch analysis techniques for heat, mass and property integration, and its visual nature facilitates planning and allows for easy communication of results to human-resource planning personnel. The method is easy to use, and can be implemented using ordinary spreadsheet software such as Excel or Lotus 123.